2010
DOI: 10.1016/j.bbi.2010.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Lack of aggression and anxiolytic-like behavior in TNF receptor (TNF-R1 and TNF-R2) deficient mice

Abstract: The mechanisms underlying violence and aggression and its control remain poorly understood. Using the Resident-Intruder paradigm, we have discovered that resident mice with combined deletion of TNF receptor type 1 (TNF-R1) and type 2 (TNF-R2) genes show a striking absence of aggressive behavior, which includes fighting, sideways postures, and tail rattling. In parallel, resident TNF-R1 and TNF-R2 knockout mice show an increase in non-aggressive exploration of the intruder mice. Given the relationship between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 30 publications
(38 reference statements)
4
37
0
Order By: Relevance
“…Excessive aggression is a symptom in a variety of neuropsychiatric disorders, such as schizophrenia, depression, anxiety disorder, and substance abuse [1]- [4], which have long been known to be associated with immune dysfunctions [5]- [8]. Consistent with clinical observations, data obtained on the basis of several animal models (isolation housing, social interactions or genetic predisposition) have indicated that aggressive behavior is accompanied with altered immune reactivity [9]- [22].…”
Section: Introductionsupporting
confidence: 66%
“…Excessive aggression is a symptom in a variety of neuropsychiatric disorders, such as schizophrenia, depression, anxiety disorder, and substance abuse [1]- [4], which have long been known to be associated with immune dysfunctions [5]- [8]. Consistent with clinical observations, data obtained on the basis of several animal models (isolation housing, social interactions or genetic predisposition) have indicated that aggressive behavior is accompanied with altered immune reactivity [9]- [22].…”
Section: Introductionsupporting
confidence: 66%
“…This pathway is essential in regulating cellular processes such as apoptosis, differentiation, immunity, and stress responses. Activating stimuli of the NF-kB pathway include interleukin 1 and tumor necrosis factor (TNF), both of which are associated with aggression [Patel et al, 2010]. Previous studies on rat have reported an association between MAPK and increased aggression scores in rat [DeMar et al, 2006;Frey et al, 2006].…”
Section: P38 Mapk Redox Signaling Pathwaymentioning
confidence: 99%
“…Mice that were null mutant for Tnfr1 also exhibited decreased immobility in both the FST and TST, relative to WT (Kaster et al, 2012). Mice that were null mutant for Tnfr1 and Tnfr2 exhibited reduced anxiety in the light-dark box test (and reduced social aggression in the resident-intruder test), relative to WT (Patel et al, 2010).…”
Section: Slc6a15mentioning
confidence: 99%